Synthesis and Evaluation of Some Uracil Nucleosides as Promising Anti-Herpes Simplex Virus 1 Agents - Samir Mohamed Awad; Shima Mahmoud Ali; Yara Essam Mansour; Samar Said Fatahala (Molecules, 2021)
Since herpes simplex virus type 1 (HSV-1) infection is so widespread, several antiviral drugs have been developed to treat it, among which are uracil nucleosides. However, there are major problems with the current medications such as severe side-effects and drug resistance. Here we present some newly synthesized cyclic and acyclic uracil nucleosides that showed very promising activity against HSV-1 compared to acyclovir.